Erectile dysfunction following pelvic fracture - Gdeh, Daou (My University, 2017)
Background: Erectile dysfunction is one of the most important sequelae of pelvic fractures and may be transient or permanent. It can range from weak erections to severe sexual dysfunctions. Importantly, erectile dysfunction is more prevalent when the pelvic fracture is associated with urethral injury. Methods:  This was a retrospective study of patient records, with a prospective questionnaire arm for patients admitted to the hospitals with a pelvic fracture between 01/07/2011 to 30/04/2015.  The electronic databases of the Orthopedic Department at Helen Joseph Hospital and the Male Sexual Dysfunction Clinic at Charlotte Maxeke Johannesburg Academic Hospital were accessed for patients' contact details, by using the name and hospital number of each patient.  Each patient was contacted telephonically with an open speaker in a presence of a witness/translator. The information sheet was read to the patient before the telephonic consent was obtained.  After consent was obtained, patients were asked to verbally complete the International Index of Erectile Function score questionnaire. Results A total of 53 patients participated in the study, of which (43.4%) reported erectile dysfunction. The majority of patients indicated a recovery of erectile function between 2 8 | P a g e to 8 months after the injury. Most were found to still suffer from other forms of sexual impairment like orgasmic dysfunction and sexual satisfaction. However, sexual desire seemed to be preserved. Patients with sexual dysfunction were more likely to have had a urethral injury as well as a more severe fracture. Conclusions In our sample of 53 patients almost half reported sexual dysfunction after a pelvic fracture. Importantly, patients with urethral damage and a severe pelvic fracture should be followed up, as the risk of sexual dysfunction is high in these particular patients.
A research report submitted to the Faculty of Health Sciences at the University of the Witwatersrand in partial fulfillment of the requirements for the qualifications of MMed (Urology) 2017
Keywords: Erectile Dysfunction Fractures